Crystal structure of the invertebrate bifunctional purine biosynthesis enzyme PAICS at 2.8 Å resolution. Issue 8 (1st June 2013) - Taschner, Michael; Basquin, Jérôme; Benda, Christian; Lorentzen, Esben
ABSTRACT: Two important steps of the de novo purine biosynthesis pathway are catalyzed by the 5‐aminoimidazole ribonucleotide carboxylase and the 4‐( N ‐succinylcarboxamide)‐5‐aminoimidazole ribonucleotide synthetase enzymes. In most eukaryotic organisms, these two activities are present in the bifunctional enzyme complex known as PAICS. We have determined the 2.8‐Å resolution crystal structure of the 350‐kDa invertebrate PAICS from insect cells ( Trichoplusia ni ) using single‐wavelength anomalous dispersion methods. Comparison of insect PAICS to human and prokaryotic homologs provides insights into substrate binding and reveals a highly conserved enzymatic framework across divergent species. Proteins 2013; 81:1473–1478. © 2013 Wiley Periodicals, Inc.